Improving job performance: workplace learning is the first step - Daryoush, Younes; Silong, Abu Daud; Omar, Zoharah; Othman, Jamilah (Australian International Academic Centre, 2013)
The present study aims to contribute new knowledge to the existing literature on workplace learning and job performance. Particularly, the study analyzes contemporary literature on workplace learning and job performance, specifically formal and informal learning as well as employee task performance and contextual performance. The study hypothesized that informal, incidental and formal workplace learning have direct positive significant relationships with employee task and contextual performance.